Investigation of Foliar L-Glutamic Application on the Resistance to the Capacity of the SC2121 Tomato Variety (Solanum lycopersicum L.) to Long-Term Salinity Stress - TURFAN, Nezahat; DÜZEL, Özlem (Yuzuncu Yil Universitesi Tarim Bilimleri Dergisi, 2023)
Within the scope of this study, the effects of L-Glutamic acid (L-GLU: 250 mg L-1, 500 mg L-1) treatments on morphological and biochemical characteristics of SC2121 tomato variety under salt stress (50 mM, 100 mM, 200 mM NaCl) were compared. The morphological results obtained from leaves and fruits were found to peak at 500GLU, 50NaCl-500GLU, 250GLU, and 200NaCl-500GLU, whereas their lowest values were achieved with doses of 200NaCl, 200NaCl-250GLU, 100NaCl, and 100NaCl-500GLU Among the bioactive molecules, amino acid, and proline amounts increased in all the treatments, whereas total protein increased in 500GLU and 50NaCl- 250GLU, 50NaCl-500GLU. CAT activity increased in doses of 500GLU and 50 NaCl-250GLU, 50NaCl-500GLU, whereas POD and SOD activity decreased in high NaCl and 200NaCl+ 250GLU, 200NaCl-500GLU. Treatments caused an increase in MDA concentration, while NaCl (50-100 mM), GLU, and 100 NaCl-500GLU reduced the H2O2 concentration. In conclusion, 500GLU, 50NaCl-500GLU, 50NaCl-250GLU, 250GLU, and 200NaCl+500GLU stimulated the growth and development in the SC2121 tomato variety, as well as the leaf bioactive chemicals. However, 200NaCl-250GLU, 200NaCl, and 200NaCl-250GLU reduced the growth and development of the tomato and decreased the chemicals in the leaves. Given the results, it can be stated that yield and quality could be increased by making use of GLU treatments in tomato varieties under salt stress.
Keywords: Chemicals; Glutamic acid; Growth; Salinity; Tomato; Bitki Bilimi; Botany; Horticultural Production; Bahçe Bitkileri Yetiştirme ve Islahı; 2. Zero hunger